MENINGKATKAN MINAT BACA MELALUI PERMAINAN TEKA TEKI SILANG DAN âBALSEM PLANGâ - Wirahyuni, Kadek (ACARYA PUSTAKA, 2017)
In the learning process, reading is something a must to do. There are many ways to increase interest in reading, including with crossword puzzles (TTS) and âbalsam plangâ or five minutes reading before going home. TTS can be categorized as a stimulant that serves to manage stress and connect the sleeping nerves of the brain. The nature of "fun" but still "learning" from TTS gives the effect of refreshing the memory, so that the work function of the brain back to optimal because the brain is accustomed to continue learning with ease. The questions in this game are related to the reading material read by the learner. Next, read the program five minutes before going home by students by reading the free reading material they choose.Keywords: reading interest, crossword game, balsem plang